Test of Acceptance and Potassium Pancake Levels of Red Bean Formulation as a Snack Alternative for Hypertension Pantients - Filisia Luna Andyana; Juliana Christyaningsih; Nurul Hindaryani; Riezky Faisal Nugroho (Journal of Nutrition Explorations, 2023)
According to the AKG (2019), the potassium requirement of adults is 4,700 mg. If a snack is given 10% of the requirement, then 470 mg is obtained per snack meal. To meet this need, an innovation of high-potassium snacks was carried out by formulating red beans in the form of flour into pancakes. The purpose of this study to determine the acceptability and potassium content of red bean pancake formulation as an alternative snack for people with hypertension. This study was an experiment on 4 different formulations with a ratio of wheat flour and red bean flour 100: 0 g, 85: 15 g, 70: 30 g, 50: 50 g, then tested for acceptability and tested for potassium levels. The highest acceptability test was in formulation 3 (PKM 3), which was 3.59 in the preferred category with a potassium content of 447.5 mg/100g. One serving of red bean pancake snack based on caloric needs obtained 80 grams for adult men with 358 mg of potassium and 67 grams for adult women with 300 mg of potassium. The highest acceptability test was in formulation 3 (PKM 3). One serving of red bean pancake snack can not meet the needs of potassium